Metazoarios parásitos de Triportheus angulatus (Spix & Agassiz,1829) "sardina" adquiridos en el mercado "Belén" Iquitos-Perú 2019 - Rengifo Chota, Heber David (2022)
In 2019, an investigation was carried out with the objective of determining the parasitic metazoans in Triportheus angulatus acquired from the "Belén" Iquitos market. Thirty individuals of T. angulatus were collected, of which the gills and the digestive tract were analyzed in order to find metazoans. The groups of identified parasites were Monogenoidea and Nematoda. Permanent slides clarified with HOYER medium were prepared from the collected monogenoids for their identification. In the case of nematodes, semi-permanent sheets clarified with lactic acid were prepared. Parasite indices and Margalef richness and Shannon diversity indices are calculated. 151 parasitic metazoan individuals were collected in Triportheus angulatus acquired from the "Belén" Iquitos market, of which 08 monogenoid species were identified; Anacanthorus acuminatus, A. chaunophallus, A. chelophorus, A. euryphallus, A lygophallus, A. pithophallus, Ancistrohaptor falciferum, A. falcunculum, 03 possible new species belonging to the genus Jainus: Jainus sp1, Jainus sp2, Jainus sp3; a species of Nematoda, Procamallanus (Spirocamallanu) inopinatus. Procamallanus (Spirocamallanus) inopinatus presented the highest prevalence 53.33% and average abundance 1.83. Jainus sp3 presented the highest average intensity 4.50. On the other hand, it was determined that there is an average richness of parasites with a value of 2,799 and a low diversity with a value of 1,966.